Design of steel-concrete composite bridges to Eurocodes - Vayas, Ioannis; Iliopoulos, Aristidis (CRC Press, Taylor & Francis Group, 2014)
"The book is aimed at students, especially at MSc level, and practicing engineers who need to become familiar with the new design rules incorporated in the EN-versions of the Eurocodes. Its focus is mainly on road bridges, although some information is provided for railway bridges. Material is presented in a concise manner"--